A Study on Occupational Pain Among Dentists of Surat City - Moradia, Sumit; Patel, Prakash (National Journal of Community Medicine, 2011)
This study has been conducted to measure prevalence of pain related to dental work among dentists in Surat city and to identify the aggravating and relieving factors associated with the pain. In this cross sectional study, 77 randomly selected dentists were interviewed. Prevalence of pain was 63.6 percent. Back was the commonest site for pain. Prolong sitting was reported to be the most common aggravating factor for pain while correcting working post relieve pain in most. Most of the dentists did not take any treatment for pain which may adversely affect the condition and increases the severity of the pain. Regular daily exercise as well as physiotherapy are helpful to relieve pain but very few doing it regularly. Some dentists took pain killers while very few consulted orthopedic surgeons for treatments.